Gandou Decoction Decreases Copper Levels and Alleviates Hepatic Injury in Copper-Laden Hepatolenticular Degeneration Model Rats - Wang, Na; Cheng, Meimei; Zhang, Xueyan; Wu, Hongfei; Wu, Huan; Cao, Shijian; Wu, Peng; Zhou, An (Frontiers in Pharmacology, 2020)
Objective: This study was designed to investigate the therapeutic efficacy and underlying mechanisms of Gandou Decoction (GDD) in copper-laden hepatolenticular degeneration model rats. Methods：In this study, high-performance liquid chromatography (HPLC) fingerprint analysis and eight representative active components were simultaneously measured for quality control of GDD. The therapeutic effect of GDD in HLD was studied by constructing a rat model of copper-laden hepatolenticular degeneration. The copper levels in the liver, serum, urine, and feces were quantified by atomic absorption spectrophotometry (AAS). Subsequently, UV-Vis spectrophotometry was used to study the coordination ability of copper ion (Cu2+) with 6 representative active components in GDD to explore its potential copper expulsion mechanism. Serological indexes including alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (AKP) were evaluated. Hepatic indicators including superoxide dismutase (SOD), glutathione (GSH) and the total antioxidant capacity (T-AOC) were determined. Moreover, the liver tissue was stained with hematoxylin-eosin (H&E) to observe the histological changes. Results：30 characteristic fingerprint peaks were used to assess the similarities among 10 samples and showed the similarity was > 0.98, indicating a good correlation among the common peaks. Simultaneous quantification of 8 markers in GDD was then performed to determine the consistency of quality. GDD could decrease the serum and hepatic copper levels through increasing the urinary and fecal copper content in copper-laden rats. Meanwhile, the results of UV-Vis absorption studies show that 6 representative active ingredients in GDD can coordinate with Cu2+, indicating that complexing copper removal may be a potential mechanism for GDD to play a role in copper removal. Serum hepatic enzyme markers AST, ALT and AKP activities and antioxidant enzyme SOD, T-AOC activities and GSH level in hepatic tissue showed the protection of GDD against liver injury induced by excessive copper. Additionally, the hepatoprotective effect of GDD was also evidenced by the results of the liver histological evaluation. Conclusions：This study suggested that GDD could reduce the serum and hepatic copper levels through promoting urinary and fecal copper excretion in copper-laden rats. At the same time, GDD could alleviate hepatic injury by inhibition of oxidative stress.